Cambrige dictionary of american english - Cambridge University Press (New York: Cambrige University Press, 2000)
Los temas principales son: Language portraits, Preface, Finding your way around the dictionary, Gramman codes, Usage labels, Parts of speech and other labels, Pronunciation symbols
Keywords: Diccionario - Inglés